2006
DOI: 10.3727/108354206778001549
|View full text |Cite
|
Sign up to set email alerts
|

Students' Travel Motivations

Abstract: The purpose of this research study was to explore travel motivations and sociodemographic characteristics of hospitality management students in Switzerland. The results of this study revealed that hospitality management students attached a high level of importance to attributes in a tourist destination such as cost/price, security, scenery, accessibility, the food and beverage experience, the lodging experience, and nightlife and entertainment facilities. It was also revealed that male students valued more ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…The current study revealed that there were significant differences based on gender regarding the push travel motivations of Omani students, which is consistent with previous studies (e.g., Hallab, Price & Fournier, 2006;McGehee, Loker-Murphy & Uysal, 1996;Rittichainuwat, 2008;Snelgrove, Taks, Chalip & Green, 2008). In particular, Omani male students were more motivated 'to experience hard adventure', 'to mix with fellow tourists', 'to watch sports events', 'to participate in physical activity', 'to be independent', as well as 'I hope that I will have some sort of romantic experience while on vacation' than the female students travelling abroad.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The current study revealed that there were significant differences based on gender regarding the push travel motivations of Omani students, which is consistent with previous studies (e.g., Hallab, Price & Fournier, 2006;McGehee, Loker-Murphy & Uysal, 1996;Rittichainuwat, 2008;Snelgrove, Taks, Chalip & Green, 2008). In particular, Omani male students were more motivated 'to experience hard adventure', 'to mix with fellow tourists', 'to watch sports events', 'to participate in physical activity', 'to be independent', as well as 'I hope that I will have some sort of romantic experience while on vacation' than the female students travelling abroad.…”
Section: Discussionsupporting
confidence: 92%
“…These results show notable similarity with previous studies (e.g., Hallab, Price & Fournier, 2006;Sangpikul, 2008). These studies have confirmed 'a variety of shopping places', 'safety and security', and 'natural attractions' as the most attractive pull travel motivations (destination's attributes) attracting tourists when they are choosing a tourist destination.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This suggests that the young Thai university students are keen to visit destinations which provide new cultural experiences, scenic values and adventure to satisfy their travel interest and affirm their intention to travel to the destination. Several studies have noted that young travellers enjoy thrill which challenges their abilities (Dotson, Clark, & Dave, 2008;Swarbrooke & Horner, 1999;Hallab, Price & Fournier, 2006;Pizam et al, 2004, Bywater, 1993 however, in the context of Thailand, insights based on current findings are new and unique.…”
mentioning
confidence: 92%
“…The extant literature acknowledges that tourist travel motivation is often pulled by destination attributes, including cost of travel (Bieger and Laesser, 2002), nightlife entertainment (Hsieh and Chang, 2006), casino gaming (Lee et al, 2006), food offerings (Rittichainuwat et al, 2008), accessibility (Hallab et al, 2006), and cultural heritage (Poria et al, 2006). These destination-specific offerings may serve as the primary or complementary factors that influence tourists' travel decisions.…”
Section: Literature Reviewmentioning
confidence: 99%